Ecotoxicological assessment of pulsed ultraviolet light‐treated water containing microbial species and Cryptosporidium parvum using a microbiotest test battery. (4th December 2013) - Garvey, Mary; Hayes, Jennifer; Clifford, Eoghan; Rowan, Neil
Abstract Development of a pulsed ultraviolet (PUV) light system as an alternative disinfection method for water treatment has been investigated, yet little is known about the impact of applying such emerging technologies on the natural aquatic environment. This study reports on the use of a battery of ecotoxicological tests representative of different ecological trophic levels to determine the safety and potability of PUV‐treated water containing known pathogens. Water samples containing Cryptosporidium oocysts and Escherichia coli were treated with PUV light, and the ecotoxicological safety was determined by assessing toxicity in a range of representative microbiotests and the Rainbow Trout Hepatocyte (RTH)‐149 fish cell line. Results show that PUV rapidly inactivated Cryptosporidium and the selected microbial species; greater rates of inactivation were observed at higher ultraviolet doses. PUV‐treated samples did not elicit ecotoxicological effects in the trophic levels studied. This study highlights that PUV is an effective means of disinfecting water containing pathogens such as Cryptosporidium.